The Influencing factors of Service Qualities on the Satisfaction of Accounting Office Services - Sukyaruke, Sasiwimon (Trends of Humanities and Social Sciences Research, 2020)
The study was carried out to examine the factors included the service qualities, the satisfaction of satisfactions, the comparison of service satisfactions of Accounting Office related to gender, age, educational background, types of business and business characters and to study o the effect of service qualities to service satisfaction of Accounting Office. A set of questionnaires was applied to analyze the data of 74 of service users of K.S.P Accounting Company Limited. The data were analyzed by applying descriptive statistics, percentage, mean and inferential statistics applying t-test, F-test (One-way ANOVA) and Regression. The findings showed that the influencing factors were as follows the service qualities, customers’ recognitions and customers’ understanding, tangibles of services, trustworthy and, reliability services and the impromptu reaction services were at high level. The high level were also focused on the service satisfaction factors of Accounting Office were on service fairness, Providing Advanced and sufficient services and timely services. The hypothesis testing by ANOVA test showed that there were not any different aspects of gender, age, education, business types and mode of business affecting the level of satisfaction of service users of Accounting Office. In addition, the Regression statistics showed that the service qualities affecting on service satisfaction of Accounting Office included the preparation of facilities for service users, the tools and equipment standard, readiness in service providing, modern and updated technology, and being a well-known office.